2007
DOI: 10.1111/j.1447-0756.2007.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral misoprostol for the prevention of primary post‐partum hemorrhage during third stage of labor

Abstract: Orally administered misoprostol was more effective in reducing blood loss during the third stage of labor than intramuscular methylergometrine. However, there were more subjects in the misoprostol group in whom duration of the third stage of labor was greater than 15 min and who also had manual placental removal than in the methylergometrine group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…Table 6 reviews studies examining the use of misoprostol in the prevention of PPH in community and hospital settings. Despite the relative superiority of conventional injectable uterotonics, to date nobody has rejected misoprostol as an appropriate drug where injectable uterotonics are not available or cannot be administered [43,[45][46][47][48][49][50][51][52]. Furthermore, systematic reviews of randomized controlled trials found decreased need for additional uterotonics when comparing misoprostol to placebo, and recommend misoprostol to be used in developing countries [45,51,52].…”
Section: Postpartum Hemorrhagementioning
confidence: 91%
“…Table 6 reviews studies examining the use of misoprostol in the prevention of PPH in community and hospital settings. Despite the relative superiority of conventional injectable uterotonics, to date nobody has rejected misoprostol as an appropriate drug where injectable uterotonics are not available or cannot be administered [43,[45][46][47][48][49][50][51][52]. Furthermore, systematic reviews of randomized controlled trials found decreased need for additional uterotonics when comparing misoprostol to placebo, and recommend misoprostol to be used in developing countries [45,51,52].…”
Section: Postpartum Hemorrhagementioning
confidence: 91%
“…In a large, multisite trial with data on measured blood loss for more than 30 000 women, the rate of postpartum bleeding ≥500 ml following oxytocin prophylaxis was 6%, with a mean blood loss of 256 ml (data not shown) 4. Studies have rarely shown oxytocin to be significantly inferior to misoprostol and in those that have, drug quality and storage conditions have been questioned 5. Indeed, analyses of the chemical potency of injectable uterotonics in other settings have shown low levels of active ingredients in the medicine 6.…”
Section: Commentarymentioning
confidence: 99%
“…Worldwide, there are an estimated 14 million pregnancy-related hemorrhages each year and 25% of maternal mortality can be attributed to post-partum hemorrhage (1). While the majority of post-partum hemorrhage leading to acute blood loss anemia is treated with red blood cell (RBC) transfusion, there remains a significant subset of patients who are unable to receive this life-saving modality.…”
Section: Introductionmentioning
confidence: 99%